Loss of the novel tumour suppressor and polarity gene Trim62 (Dear1) synergizes with oncogenic Ras in invasive lung cancer. Issue 1 (16th July 2014) - Quintás‐Cardama, Alfonso; Post, Sean M; Solis, Luisa M; Xiong, Shunbin; Yang, Peirong; Chen, Nanyue; Wistuba, Ignacio I; Killary, Ann M; Lozano, Guillermina
Abstract Deregulation of cell polarity proteins has been linked to the processes of invasion and metastasis. TRIM62 is a regulator of cell polarity and a tumour suppressor in breast cancer. Here, we demonstrate that human non‐small cell lung cancer lesions show a step‐wise loss of TRIM62 levels during disease progression, which was associated with poor clinical outcomes. To directly examine the role of Trim62 in development of lung cancer, we deleted Trim62 in a mutant K‐Ras mouse model of lung cancer. In this context, haploinsufficiency of Trim62 synergized with a K‐RasG12D mutation to promote invasiveness and disrupt three‐dimensional morphogenesis, both of which are associated with epithelial–mesenchymal transitions. Re‐expression of Trim62 reverted these phenotypes in tumour cell lines. Thus, Trim62 loss cooperates with K‐Ras mutation in tumourigenesis and metastasis in vivo, indicating that decreased levels of TRIM62 may play an important role in the evolution of lung cancer. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.